2020
DOI: 10.1021/acssuschemeng.0c05272
|View full text |Cite
|
Sign up to set email alerts
|

CeO2 Nanoparticle-Decorated Co3O4 Microspheres for Selective Oxidation of Ethylbenzene with Molecular Oxygen under Solvent- and Additive-Free Conditions

Abstract: An ideal catalytic process for the selective oxidation of hydrocarbons should employ an efficient, recyclable, and cost-effective catalyst under solvent- and additive-free conditions with molecular oxygen as the only oxidant. This is an important goal in the catalysis community and remains a significant challenge. In this respect, we report the facile construction of a series of uniform CeO2 nanoparticle-decorated Co3O4 microspheres (CeO2/Co3O4) for the selective ethylbenzene oxidation reaction by molecular ox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
38
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(38 citation statements)
references
References 66 publications
(87 reference statements)
0
38
0
Order By: Relevance
“…Compared with the expensive noble metals, CeO 2 -based transition metal catalysts have attracted large attention due to their cost-effective performance. , Doping CeO 2 with transition-metal atoms into the ceria lattice is another widely adopted strategy to further decrease the energy barrier for oxygen vacancy formation, promote O 2 activation and lattice oxygen mobility, which could enhance the catalytic activity for selective oxidation of hydrocarbons. The active electron-deficient metal species such as Cu + , Co 2+ , Cr 3+ , Mn 4+ , and Ce 3+ activate the dissociation of C–H bonds and O 2 .…”
Section: Ceria-based Catalysts For Selective Oxidation Via Thermocata...mentioning
confidence: 99%
See 1 more Smart Citation
“…Compared with the expensive noble metals, CeO 2 -based transition metal catalysts have attracted large attention due to their cost-effective performance. , Doping CeO 2 with transition-metal atoms into the ceria lattice is another widely adopted strategy to further decrease the energy barrier for oxygen vacancy formation, promote O 2 activation and lattice oxygen mobility, which could enhance the catalytic activity for selective oxidation of hydrocarbons. The active electron-deficient metal species such as Cu + , Co 2+ , Cr 3+ , Mn 4+ , and Ce 3+ activate the dissociation of C–H bonds and O 2 .…”
Section: Ceria-based Catalysts For Selective Oxidation Via Thermocata...mentioning
confidence: 99%
“…Compared with the expensive noble metals, CeO 2 -based transition metal catalysts have attracted large attention due to their cost-effective performance. , Doping CeO 2 with transition-metal atoms into the ceria lattice is another widely adopted strategy to further decrease the energy barrier for oxygen vacancy formation, promote O 2 activation and lattice oxygen mobility, which could enhance the catalytic activity for selective oxidation of hydrocarbons. The active electron-deficient metal species such as Cu + , Co 2+ , Cr 3+ , Mn 4+ , and Ce 3+ activate the dissociation of C–H bonds and O 2 . For instance, Zhang et al synthesized a mesoporous Mn 0.5 Ce 0.5 O x solid solution with maximized active surface oxygens and highly reducible Mn 4+ ions via a simple self-assembly method with ionic liquids, which had high catalytic activity and selectivity (17.7% conversion and 81% selectivity for KA oils) for the selective oxidation of cyclohexane to KA oils at 100 °C for 12 h under 10 bar O 2 .…”
Section: Ceria-based Catalysts For Selective Oxidation Via Thermocata...mentioning
confidence: 99%
“…To further determine the structural distortion of the as-synthesized samples, the samples Co 1 Ce 2 O x , Co 1 Ce 1 O x , and Co 2 Ce 1 O x were characterized by Raman spectroscopy and the results are shown in Figure . It can be observed that bare CeO 2 shows a strong peak centered at 465 cm –1 , which can be attributed to the strong F 2g mode of the fluorite phase, while pure Co 3 O 4 shows four peaks at 190, 480, 520, and 690 cm –1 , corresponding to F 2g 1 , E g , F 2g , A 1g and F 2g phonon modes, which is indicative of a spinel structure for Co 3 O 4 . , However, as for the Co–CeO x catalysts, the peaks of all Co–CeO x catalysts become more asymmetric, weaker, and broader, and F 2g shifts to lower frequencies. This phenomenon indicates that Co could induce a lattice distortion or structural disorder of the fluorite structure of CeO 2 , which is due to the reason that Co can enter the CeO 2 lattice to form Ce 1– x Co x O 2 solid solution.…”
Section: Results and Discussionmentioning
confidence: 94%
“…2g phonon modes, which is indicative of a spinel structure for Co 3 O 4 46,47. However, as for the Co−CeO x catalysts, the peaks of all Co−CeO x catalysts become more asymmetric, weaker, and broader, and F 2g shifts to lower frequencies.…”
mentioning
confidence: 89%
“…[ 3–9 ] Compared with their bulk counterparts, functional nanoparticles possess high surface‐to‐volume ratios, rich active surface atoms and unique electronic structures, which have been well demonstrated very effective in catalysis. [ 10,11 ] However, owing to their high surface energy, functional nanoparticles are thermodynamically unstable and prone to migration and coalescence in the catalytic process, thereby resulting in a sharply decrease in the activity and selectivity, especially at high reaction temperatures. [ 12–14 ] In this regard, incorporation of functional nanoparticles into support materials is expected to enhance their catalytic stability because supports physically isolate the functional nanoparticles and prevent them from migration and coalescence.…”
Section: Introductionmentioning
confidence: 99%